Ethylene vinyl alcohol copolymer composition and composite woven fabric comprising the same

The EVOH composition modified with maleic acid monomer units and metal ions addresses the adhesion and washing resistance issues of EVOH compositions, enhancing their performance in composite fabrics by maintaining cooling properties and surface quality after multiple washings.

JP2025043254AActive Publication Date: 2025-03-28CHANG CHUN PETROCHEMICAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024076746
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-15
Filing Date
2024-05-09
Publication Date
2025-03-28
Estimated Expiration
2044-05-09

AI Technical Summary

Technical Problem

Ethylene-vinyl alcohol copolymer (EVOH) compositions face challenges in adhering to fabrics and maintaining cooling properties after multiple washings, limiting their use in the spinning industry.

Method used

An EVOH composition modified with maleic acid monomer units and metal ions, specifically copper ions, is developed to enhance adhesion to fabrics and improve washing resistance while maintaining surface properties.

Benefits of technology

The modified EVOH composition effectively reduces the impact of washing on cooling properties, enhances washing resistance, and maintains ideal surface properties, making it suitable for use in composite fabrics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025043254000001
    Figure 2025043254000001
  • Figure 2025043254000002
    Figure 2025043254000002
  • Figure 2025043254000003
    Figure 2025043254000003
Patent Text Reader

Abstract

To provide an ethylene vinyl alcohol copolymer composition and a composite woven fabric comprising the same.SOLUTION: The present invention provides an ethylene-vinyl alcohol copolymer (EVOH) composition comprising an ethylene-vinyl alcohol copolymer modified with a maleic acid monomer unit and a metal ion. The present invention provides a composite woven fabric, which has the composition distributed on the woven fabric. The invention also provides a composite woven fabric with a rate of change in the cool feeling parameter of 5% or less after washing. The present invention further provides a composite fiber comprising a fiber and the composition, wherein the fiber is impregnated with the composition so that the composition is distributed on the fiber. When the ethylene-vinyl alcohol copolymer composition of the present invention is distributed on the woven fabric or fiber, the composite woven fabric not only can reduce the influence of washing on the cool feeling property, thereby improving the washing resistance, but also has good surface properties.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to ethylene-vinyl alcohol copolymer compositions and composite fabrics containing same, but the invention is not limited thereto. [Background technology]

[0002] Ethylene-vinyl alcohol copolymer (EVOH) has a wide range of applications in laminates that preserve perishable goods due to its properties such as good transparency, gas barrier properties, solvent / oil resistance, and mechanical strength. For example, EVOH copolymers and laminates are commonly used in the food packaging industry, medical device and consumables industry, pharmaceutical industry, electronics industry, and agrochemical industry. Specifically, EVOH is usually incorporated into laminates as a separate layer that functions as an oxygen barrier layer.

[0003] At the same time, ethylene-vinyl alcohol copolymer has good biocompatibility and skin-friendly cool touch properties, so it can be used not only in hemodialysis membranes but also in textiles, for example, by incorporating it into fabrics to make functional composite fabrics such as cool clothing and quick-drying clothing. Summary of the Invention [Problem to be solved by the invention]

[0004] However, although the EVOH composition has a skin-friendly cool touch property, the present inventors found that when the EVOH composition is dispersed on a textile, it is difficult for the composition to adhere to the textile, so that the cool touch property of the composite textile after multiple washings is greatly affected, and therefore the use of the EVOH composition in the textile industry is still limited. [Means for solving the problem]

[0005] In order to solve the above technical problems, one aspect of the present invention provides an ethylene-vinyl alcohol copolymer (EVOH) composition comprising an ethylene-vinyl alcohol copolymer modified with maleic acid monomer units and a metal ion.

[0006] According to one embodiment of the present invention, the maleic acid monomer unit content is 0.05 to 0.49 mol %.

[0007] According to one embodiment of the present invention, the content of the maleic acid monomer unit is 0.1 to 0.49 mol %.

[0008] According to one embodiment of the present invention, the metal ion content is 0.05 to 100 ppm.

[0009] According to one embodiment of the present invention, the metal ion content is 0.1 to 80 ppm.

[0010] According to one embodiment of the invention, the metal ions are copper ions.

[0011] According to one embodiment of the present invention, the metal ion is a divalent copper ion.

[0012] According to one embodiment of the present invention, the ethylene content of the composition is 24-48 mol %.

[0013] According to one embodiment of the present invention, the saponification degree of the composition is greater than 99.5 mol %.

[0014] According to one embodiment of the present invention, the volatile content of the composition is 10 to 90%.

[0015] Another aspect of the present invention provides a composite fabric comprising a fabric and the composition distributed in the fabric, the composite fabric has a cooling parameter change rate of 5% or less after washing, the cooling parameter is measured according to the method described in FTTS-FA-019-2013, and the cooling parameter change rate after washing is calculated by the following formula, where L0 is the cooling parameter after 0 washes, and L30 is the cooling parameter after 30 washes, and the washing is performed according to the method described in JIS L 0217-103.

[0016]

number

[0017] According to one embodiment of the invention, the composition is applied to the surface of the textile.

[0018] According to one embodiment of the invention, the fabric is impregnated with the composition so as to distribute the composition on the fabric.

[0019] According to one embodiment of the present invention, the fabric is woven from nylon, polyethylene, polyester, rayon, natural fibers or mixtures thereof.

[0020] According to one embodiment of the present invention, the composition is prepared in a 3-10% by weight solution and then distributed on the fabric.

[0021] In a further aspect of the present invention, there is provided a composite fiber comprising a fiber and the composition as described above, the fiber being impregnated with the composition so as to distribute the composition on the fiber.

[0022] In yet another aspect of the present invention, there is provided a woven fabric comprising the bicomponent fiber described above. Effect of the Invention

[0023] The advantage of the present invention is that the ethylene-vinyl alcohol copolymer composition of the present invention, when distributed on a fabric or fiber, can not only reduce the effect of cool feeling caused by washing, but also improve the washing resistance, and has good surface properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The following embodiments should not be considered as unduly limiting the present invention. Those skilled in the art may make modifications and variations to the embodiments described herein without departing from the spirit or scope of the present invention, and such modifications and variations fall within the scope of the present invention.

[0025] As used herein, unless the context dictates otherwise, the terms "comprise", "include", "comprises", "has" or "containing" are inclusive or open-ended and do not exclude other unrecited elements or method steps, and the terms "a" and "the" may be interpreted as singular or plural, and the term "one or more" means "at least one", and therefore may include a single feature or a mixture / combination. In addition, in this specification and the appended claims, unless otherwise specified, "distributed on something" may be considered to be directly or indirectly contacting the surface of an object through attachment or other forms, and the identification of said surface shall be determined based on the meaning of the surrounding context / paragraph of the specification and the common knowledge in the field to which this specification pertains.

[0026] One aspect of the present invention provides a composition of ethylene-vinyl alcohol copolymer (EVOH) comprising an ethylene-vinyl alcohol copolymer modified with maleic acid monomer units and a metal ion.

[0027] As used herein, the term "maleic acid monomer unit" refers to a monomer unit derived from maleic acid, maleic anhydride, maleic acid monomethyl ester, maleic acid monoethyl ester, or maleic acid diethyl ester. In a preferred embodiment, the maleic acid monomer unit is derived from maleic anhydride. Without being bound by any particular theory, the inventors believe that the addition of maleic acid monomer units during the formation of EVOH to form an ethylene-vinyl alcohol copolymer modified with maleic acid monomer units (also called "maleic acid modified EVOH") creates strong interactive groups between the EVOH composition and the textile / fiber, thereby enhancing the degree of intimate bonding between the composition and the textile / fiber, and also improving the washability of the finished composite textile.

[0028] As used herein, the term "metal ion" refers to a metal ion that can form a coordinate bond with maleic acid monomer to stabilize polymer molecules, and is not particularly limited. In a preferred embodiment of the present invention, the metal ion is a copper ion, such as a monovalent copper ion, a divalent copper ion, a trivalent copper ion, or a tetravalent copper ion. More preferably, the metal ion is a divalent copper ion. Without being bound by a particular theory, the present inventors have further found that the addition of maleic acid monomer units can certainly improve the wash resistance of the composite textile finished product, but the monomer units may undergo a self-crosslinking reaction to form a gel on the surface of the composite textile finished product, thereby deteriorating the surface properties. After further testing, the present inventors have found that when metal ions are added to the EVOH composition, the entire EVOH composition can be effectively stabilized and the surface of the composite textile finished product can be made smooth by avoiding deterioration. In other words, the EVOH composition of the present invention, which contains both an ethylene-vinyl alcohol copolymer modified with maleic acid monomer units and metal ions, can be distributed on the textile / fiber to not only effectively improve the wash resistance but also have good surface properties.

[0029] According to at least one embodiment of the present invention, the maleic acid monomer unit content is 0.05 to 0.49 mol%, and is a value within a range between any two of the following values, such as, but not limited to, 0.05 mol%, 0.06 mol%, 0.07 mol%, 0.08 mol%, 0.09 mol%, 0.1 mol%, 0.13 mol%, 0.16 mol%, 0.19 mol%, 0.2 mol%, 0.23 mol%, 0.26 mol%, 0.29 mol%, 0.3 mol%, 0.33 mol%, 0.36 mol%, 0.39 mol%, 0.4 mol%, 0.43 mol%, 0.46 mol% and 0.49 mol%. In a preferred embodiment, the maleic acid monomer unit content is 0.1 to 0.49 mol%.

[0030] According to at least one embodiment of the present invention, the metal ion content is 0.05 to 100 ppm, and is a value within a range between any two of the following values, such as, but not limited to, 0.05 ppm, 0.1 ppm, 0.5 ppm, 1 ppm, 5 ppm, 10 ppm, 15 ppm, 20 ppm, 25 ppm, 30 ppm, 35 ppm, 40 ppm, 45 ppm, 50 ppm, 55 ppm, 60 ppm, 65 ppm, 70 ppm, 75 ppm, 80 ppm, 85 ppm, 90 ppm, 95 ppm, and 100 ppm. In a preferred embodiment, the metal ion content is 0.1 to 80 ppm.

[0031] According to at least one embodiment of the present invention, the ethylene-vinyl alcohol copolymer modified with maleic acid monomer units has an ethylene content of 24 to 48 mol%, and the ethylene content is within a range between any two of the following values, such as, but not limited to, 24 mol%, 25 mol%, 26 mol%, 27 mol%, 28 mol%, 29 mol%, 30 mol%, 31 mol%, 32 mol%, 33 mol%, 34 mol%, 35 mol%, 36 mol%, 37 mol%, 38 mol%, 39 mol%, 40 mol%, 41 mol%, 42 mol%, 43 mol%, 44 mol%, 45 mol%, 46 mol%, 47 mol% and 48 mol%.

[0032] According to one embodiment of the present invention, the saponification degree of the ethylene-vinyl alcohol copolymer modified with the maleic acid monomer unit is greater than 99.5 mol%, for example, greater than 99.5 mol%, 99.6 mol% or more, 99.7 mol% or more, 99.8 mol% or more, or 99.9 mol% or more, but not limited thereto.

[0033] The compositions of the present invention typically have a volatile content in a certain range, for example the volatile content of the composition is 10-90%, and may be any value within a range between any two of the following values, such as, but not limited to, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% and 90%. The volatile content is determined by analyzing the final ethylene-vinyl alcohol copolymer obtained using the method described in ISO 14663-2 Annex A.

[0034] The EVOH composition of the present invention can be in the form of pellets, films, fibers, solutions, etc. According to at least one embodiment of the present invention, the EVOH composition of the present invention is in the form of particles, and the EVOH composition is granulated to form one or more particle shapes and / or shapes. Although the EVOH composition is described herein as being granulated to form one or more pellets, the EVOH composition may be processed into beads, cubes, chips, shavings, etc. In some embodiments, the pellet shape of the EVOH composition can be cylindrical, round granular, or flat, the cylindrical shape can be cylindrical, elliptical cylindrical, or rectangular, and the round granular shape can be spherical, elliptical, or go stone-shaped.

[0035] Another aspect of the present invention provides a composite fabric comprising a fabric and the aforementioned composition distributed on the fabric. The change rate of the cooling sensation parameter of the composite fabric after washing is 5% or less, for example, but not limited to, 5%, 4.5%, 4%, 3.5%, 3%, 2.5%, 2%, 1.5% or 1%. Specifically, the present invention evaluates the washing resistance performance of the fabric by testing the change rate of the cooling sensation parameter of the fabric after washing. The cooling sensation parameter is the maximum heat loss value per unit area (W / cm2) when the fabric simulated by the instrument is brought into contact with the surface of the human body. 2 ) and is an index of the cool sensation performance of a woven fabric. The cool sensation parameter in this specification is measured in accordance with the method described in FTTS-FA-019-2013, and the rate of change in the cool sensation parameter after washing is calculated by the following formula, in which L0 represents the cool sensation parameter after 0 washes and L30 represents the cool sensation parameter after 30 washes, and the washing is carried out in accordance with the method described in JIS L 0217-103.

[0036]

number

[0037] After multiple washings, the cool sensation parameter of the composite fabric of the present invention has a change rate within a certain range (i.e., 5% or less) compared to before washing, in other words, the composite fabric of the present invention has a certain degree of washing resistance.

[0038] As used herein, the term "woven fabric" refers to either a knitted fabric or a woven fabric, preferably composed of a fast heat absorbing, highly heat conductive texture, such as, but not limited to, highly heat conductive nylon, polyethylene fiber, polyester fiber, polyamide fiber, polyacrylonitrile fiber, polypropylene fiber, rayon, natural fiber (cotton, linen, wool, etc.), or a mixture of these fiber materials. In a preferred embodiment, the woven fabric is woven from nylon, polyethylene, polyester, rayon, natural fiber, or a mixture of these. The weaving structure of the woven fabric is not particularly limited, and various weaving forms such as plain weave, twill weave, satin weave, leno weave, imitation leno weave, twill weave, etc. can be used.

[0039] According to one embodiment of the present invention, the composition is applied onto the surface of the textile. According to another embodiment of the present invention, the textile is impregnated with the composition so that the composition is distributed on the textile, and the concentration of the composition is not limited. Experiments have shown that after a solution of a low concentration of the composition is obtained, the amount of the composition can be reduced to give the textile washability and cool feeling properties. Specifically, the composition is preferably formulated into a 3-10% by weight solution (for example, a value within any two of the following values, 3% by weight, 3.5% by weight, 4% by weight, 4.5% by weight, 5% by weight, 5.5% by weight, 6% by weight, 6.5% by weight, 7% by weight, 7.5% by weight, 8% by weight, 8.5% by weight, 9% by weight, 9.5% by weight and 10% by weight, but not limited thereto), and then applied or impregnated onto the textile. When the composition is mixed into a solution, the solvent that can be used is not particularly limited as long as it can dissolve or disperse the EVOH composition, but from the viewpoints of safety (from the viewpoints of boiling point, toxicity, etc.), ease of the subsequent drying process, and operation, water or an aqueous alcohol solution (such as, but not limited to, an aqueous methanol solution, an aqueous ethanol solution, an aqueous isopropyl alcohol solution, etc.) is preferred. After the composition is made into a solution, the thickness formed by coating or impregnation on the woven fabric is not particularly limited, and the required thickness can be adjusted as necessary, but for example, the thickness of the woven fabric after drying is 0.01 to 1 mm.

[0040] In a further aspect of the present invention, there is provided a composite fiber comprising a fiber and the composition as described above. The fiber is impregnated with the composition so as to distribute the composition on the fiber. As used herein, the term "fiber" refers to a fiber material that is not woven into a fabric, such as, but not limited to, spun fibers. Preferably, the fiber is a fast heat absorbing, highly thermally conductive material, such as, but not limited to, highly thermally conductive nylon, polyethylene fiber, polyester fiber, polyamide fiber, polyacrylonitrile fiber, polypropylene fiber, rayon, natural fiber (cotton, linen, wool, etc.), or a fiber material after blending thereof. In a preferred embodiment, the fiber comprises nylon, polyethylene, polyester, rayon, natural fiber, or a blend thereof.

[0041] According to one embodiment of the present invention, it is preferable to mix the composition into a 3-10 wt% solution (for example, a value within a range between any two of the following values, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.5 wt%, 9 wt%, 9.5 wt%, and 10 wt%), and then impregnate the fabric with the solution. When mixing the composition into a solution, the solvent that can be used is not particularly limited as long as it can dissolve or disperse the EVOH composition, but from the viewpoints of safety (from the viewpoints of boiling point, toxicity, etc.), subsequent drying process, and ease of operation, water or an aqueous alcohol solution (for example, an aqueous methanol solution, an aqueous ethanol solution, an aqueous isopropyl alcohol solution, etc., but not limited thereto) is preferable. After the composition is made into a solution, the fiber is impregnated with the solution to make the composite fiber have a core-shell structure, and the composite fiber can be further woven (for example, by wrapping or braiding, but not limited thereto) to form a woven fabric. The thickness of the composite fiber is also not particularly limited, and can be adjusted to a required thickness (for example, 0.001 to 1 mm) as needed. The thickness of the woven fabric woven with the composite fiber is not particularly limited, and can be adjusted to a required thickness (for example, 0.01 to 1 mm) as needed. EXAMPLES

[0042] The present invention will be described in detail below with reference to specific examples. However, it should be understood that these examples are intended to aid in the understanding of the present invention and are not intended to limit the scope of the present invention in any way.

[0043] 1. Preparation of Ethylene-Vinyl Alcohol Copolymer (EVOH) Composition The following provides non-limiting methods of preparation of the EVOH compositions herein, where the EVOH compositions of six non-limiting Examples (Examples 1-6) and eleven Comparative Examples (Comparative Examples 1-11) were all prepared using the methods below (or methods similar to the methods below).

[0044] First, maleic anhydride (specific amounts used are as follows), 1100g of vinyl acetate, 182.3g of methanol, 85g of peroxide initiator, and 1.975g of citric acid were added to a small polymerization kettle equipped with a jacket, and the inside of the polymerization kettle was once replaced with nitrogen, then replaced with ethylene, and pressurized until the ethylene pressure reached a predetermined pressure (specific values ​​will be described later). Under the condition of maintaining the ethylene pressure, the temperature was raised to 60°C while stirring to start polymerization. 8 hours after the start of polymerization, when the solid concentration reached 40%, 46.6kg of polymerization inhibitor was added. In this way, a maleic acid-ethylene-vinyl acetate copolymer having a specific maleic acid monomer unit content and ethylene content was obtained. Next, the reaction liquid containing the copolymer was fed to a small distillation column, methanol was added and the temperature was raised to remove unreacted vinyl acetate, and a methanol solution of the copolymer and maleic acid monomer units was obtained, which was alkalized with NaOH at 55°C to obtain a maleic acid-ethylene-vinyl alcohol copolymer with a saponification degree exceeding 99.5%. The pellets were fed into an inlet pipe with a diameter of 2.8 mm, cut with a rotary blade at 1500 rpm, and cooled by adding water at 5°C to the maleic acid-ethylene-vinyl alcohol copolymer pellets. The maleic acid-ethylene-vinyl alcohol copolymer pellets were then washed with water to remove unpolymerized third monomer, and dehydrated to separate the maleic acid-ethylene-vinyl alcohol copolymer particles. The particles were then immersed in a copper acetate aqueous solution of a specific concentration for a certain period of time, and then dehydrated to obtain maleic acid-ethylene-vinyl alcohol copolymer particles with a specific copper content, and finally the volatile content was adjusted to obtain the finished EVOH composition.

[0045] Using the above method, the amount of maleic anhydride used, ethylene pressure, copper acetate concentration and impregnation time in the manufacturing process of each example are different, so the ethylene content, maleic acid monomer unit content and copper ion content are different. The specific differences are as follows:

[0046] Example 1 The preparation method of Example 1 was as described above, except that Example 1 used 25.2 g of maleic anhydride and the ethylene pressure was 36.5 kg / cm2 The concentration of copper acetate was 0.001% by weight, and the impregnation time of copper acetate was 0.5 hours.

[0047] Example 2 The preparation method of Example 2 was as described above, except that Example 2 used 70.1 g of maleic anhydride and the ethylene pressure was 36.5 kg / cm 2 The concentration of copper acetate was 0.001 wt %, and the impregnation time of copper acetate was 2.5 hours.

[0048] Example 3 The preparation method of Example 3 was as described above, except that Example 3 used 115.5 g of maleic anhydride and the ethylene pressure was 36.5 kg / cm 2 The concentration of copper acetate was 0.020 wt %, and the impregnation time of copper acetate was 24 hours.

[0049] Example 4 The preparation method of Example 4 was as described above, except that in Example 4, 120.3 g of maleic anhydride was used and the ethylene pressure was 48.0 kg / cm 2 The concentration of copper acetate was 0.040 wt %, and the impregnation time of copper acetate was 16 hours.

[0050] Example 5 The preparation method of Example 5 was as described above, except that Example 5 used 70.5 g of maleic anhydride and the ethylene pressure was 60.0 kg / cm. 2 The concentration of copper acetate was 0.020 wt %, and the impregnation time of copper acetate was 10 hours.

[0051] Example 6 The preparation method of Example 6 was as described above, except that Example 6 used 70.1 g of maleic anhydride and the ethylene pressure was 60.0 kg / cm 2 The concentration of copper acetate was 0.020 wt %, and the impregnation time of copper acetate was 10 hours.

[0052] Using the above method, the amount of maleic anhydride used, ethylene pressure, copper acetate concentration and impregnation time in the production process of each comparative example are different, so the ethylene content, maleic acid monomer unit content and copper ion content are different. The specific differences are as follows:

[0053] Comparative Example 1 The preparation method of Comparative Example 1 was as described above. However, in Comparative Example 1, the ethylene pressure was 36.5 kg / cm 2 and no maleic anhydride and no copper acetate were added.

[0054] Comparative Example 2 The preparation method of Comparative Example 2 was as described above, except that in Comparative Example 2, 25.5 g of maleic anhydride was used, and the ethylene pressure was 36.5 kg / cm 2 and no copper acetate was added.

[0055] Comparative Example 3 The preparation method of Comparative Example 3 was as described above, except that in Comparative Example 3, 114.8 g of maleic anhydride was used, and the ethylene pressure was 36.5 kg / cm. 2 and no copper acetate was added.

[0056] Comparative Example 4 The preparation method of Comparative Example 4 was as described above, except that in Comparative Example 4, 160.1 g of maleic anhydride was used, and the ethylene pressure was 36.5 kg / cm 2 The concentration of copper acetate was 0.05 wt %, and the impregnation time of copper acetate was 24 hours.

[0057] Comparative Example 5 The preparation method of Comparative Example 5 was as described above, except that in Comparative Example 5, 160.3 g of maleic anhydride was used, and the ethylene pressure was 36.5 kg / cm 2 The concentration of copper acetate was 0.04 wt %, and the impregnation time of copper acetate was 16 hours.

[0058] Comparative Example 6 The preparation method of Comparative Example 6 was as described above, except that in Comparative Example 6, 230.5 g of maleic anhydride was used, and the ethylene pressure was 36.5 kg / cm 2 The concentration of copper acetate was 0.05 wt %, and the impregnation time of copper acetate was 24 hours.

[0059] Comparative Example 7 The preparation method of Comparative Example 7 was as described above. However, in Comparative Example 7, the ethylene pressure was 48 kg / cm 2 and no maleic anhydride and no copper acetate were added.

[0060] Comparative Example 8 The preparation method of Comparative Example 8 was as described above. However, in Comparative Example 8, 229.8 g of maleic anhydride was used, and the ethylene pressure was 48.0 kg / cm. 2 and no copper acetate was added.

[0061] Comparative Example 9 The preparation method of Comparative Example 9 was as described above. However, in Comparative Example 9, the ethylene pressure was 60.0 kg / cm 2 and no maleic anhydride and no copper acetate were added.

[0062] Comparative Example 10 The preparation method of Comparative Example 10 was as described above. However, in Comparative Example 10, 160.9 g of maleic anhydride was used, and the ethylene pressure was 60.0 kg / cm. 2 The concentration of copper acetate was 0.06 wt %, and the impregnation time of copper acetate was 20 hours.

[0063] Comparative Example 11 The preparation method of Comparative Example 11 was as described above. However, in Comparative Example 11, 70.8 g of maleic anhydride was used, and the ethylene pressure was 60.0 kg / cm. 2 The concentration of copper acetate was 0.07 wt %, and the impregnation time of copper acetate was 24 hours.

[0064] 2. Analysis and Measurement Methods The measurement methods for the parameters and properties of the EVOH compositions and composite fabrics made therefrom in Examples 1 to 6 and Comparative Examples 1 to 11 are shown below. Tables 1 and 2 further show the parameters and properties of each of these Examples and Comparative Examples, as well as the characteristic evaluation of the composite fibers.

[0065] 2-1.Method of analysis of ethylene content In the present invention, in order to evaluate / analyze the ethylene content of the EVOH compositions of the Examples and Comparative Examples, the ethylene content was randomly measured at five points in each EVOH composition sample using a UniDRON Raman spectrometer with a laser light source having a wavelength of 473 nm, and the average value was taken as the ethylene content value of the EVOH composition sample.

[0066] 2-2. Measurement method for maleic acid monomer unit content Approximately 2000 mg of the EVOH composition was dissolved in 75 ml of dimethylacetamide (DMAc) and 2 to 3 drops of phenolphthalein were added as an indicator to serve as the experimental group, which was then titrated with 0.1 M NaOH. When the titration end point was reached, the amount of 0.1 M NaOH used was recorded. A group in which only DMAc solvent was used was used as the blank group, and the amount used in the blank group was subtracted from the experimental group to back-estimate the proportion of maleic acid monomer units.

[0067] 2-3.Metal ion content measurement method After drying the hydrous EVOH composition sample, 0.2 g of the sample was taken and 10 ml of nitric acid was added to dissolve the sample (also called wet decomposition). The liquid after the decomposition was then diluted with ion-exchanged water to a total liquid volume of 50 ml. The metals in the diluted solution were quantitatively analyzed using an ICP optical emission spectrometer (Thermofisher iCAP® 7400 ICP-OES). The metal compound content was calculated based on the elemental equivalent value. For the quantification, a calibration curve created from a commercially available copper ion standard solution (ISE standard Cu) was used.

[0068] 2-4.Measuring method of saponification degree In this specification, the degree of saponification of each EVOH composition was measured in accordance with the method described in ISO 14663-2:1999.

[0069] 2-5. Analysis and evaluation of coating surface condition A 40 x 25 cm plain weave nylon fabric was coated with a woven fabric (Q-MAX: 0.11 W / cm 2 ), then the EVOH composition was mixed with an aqueous alcohol solution prepared by mixing methanol and water in a specific ratio to prepare a solution with a concentration of 5 wt%, which was then applied with a scraper (wet coating thickness 0.1 mm), and finally, the product was pre-dried at 60°C for 5 minutes, dried at 120°C for 5 minutes, and molded at 140°C for 1 minute to finally form a composite woven product. The surface condition of the composite woven product was evaluated visually and by touch, and a mark of "○" was given when the coating area was smooth, and a mark of "×" was given when gel remained on the surface of the woven product.

[0070] [Table 1]

[0071] 2-6-1. Analysis and evaluation of washing durability - Cool sensation parameters As described herein, the wash resistance of the composite fabric is based on the rate of change in the coolness parameter after washing. First, for the measurement of the coolness parameter, the present invention was tested using a thermal property measuring device KES-F7 THERMO LABO II or an equivalent test device in accordance with the standard method described in FTTS-FA-019-2013. Here, the test sample is the same as the finished composite fabric in the above paragraph, and five square pieces of 20 cm x 20 cm (actual area 5 cm x 5 cm) are taken per piece, and can be tested by placing them in an environment of 20 ± 2 ° C and 65 ± 2% RH for 24 hours. After checking the parameters, the samples were heated for about 15 minutes, the temperature of the hot plate (Temperature-Box) was set to 35.0 ± 0.1 ° C, and when it reached 35.0 ± 0.1 ° C, the Guard Heater switch was switched to the start position (ON). The temperature of the cold plate (Water Box) was set to 25.0±0.1°C (simulating an external environment). After the temperature reached 25.0±0.1°C, the sample was placed on the cold plate with the EVOH composition applied side (skin contact side) facing up. When the temperature of the hot plate reached the set temperature of 35.0±0.1°C, the qm key was pressed and the hot plate was quickly placed on the sample, and the qm value on the monitor was recorded. This value is the maximum value of heat loss at the moment of contact with the fabric, which is the result of the cool sensation experiment, and is expressed in units of W / cm. 2 It was decided.

[0072] 2-6-2. Analysis and evaluation of washing durability - rate of change in cool sensation parameters After knowing the method for measuring the cool sensation parameter, it is necessary to further analyze the change rate of the cool sensation parameter in order to evaluate the washing resistance performance of the composite fabric finished product. The formula for the change rate of the cool sensation parameter is as follows:

[0073]

number

[0074] [Table 2]

[0075] [Table 3]

[0076] According to the results shown in Tables 1 and 2, when the EVOH composition does not contain maleic acid monomer units, even if the surface properties of the composite fabric made therefrom are ideal, the wash resistance is poor, as can be seen from Comparative Examples 1, 7, and 9. When maleic acid monomer units are contained, the composite fiber finished product has good wash resistance, but the monomer units may undergo a self-crosslinking reaction on the surface to form a gel, resulting in poor surface properties, as can be seen from Comparative Examples 2-6, 8, and 10-11.

[0077] As described herein, it is believed that when the EVOH composition contains maleic acid monomer units, but also contains metal ions, it is possible to effectively stabilize the entire EVOH composition and avoid deterioration, thereby smoothing the surface of the composite textile finished product. A detailed look at Tables 1 and 2 shows that the EVOH compositions of Examples 1 to 6 all contain maleic acid monomer units and metal ions, so that the composite textiles made from these compositions have both good wash resistance and surface properties. However, as can be seen from a comparison between Examples 5 and 6 and Comparative Example 11, even when both maleic acid monomer units and metal ions are contained, when the metal ion content of Comparative Example 11 exceeds the upper limit, the surface properties of the composite textile finished product are poor. Without being bound by a particular theory, it is believed that this result is probably due to the fact that when the metal ion content exceeds the upper limit, impurities are formed and gel is generated, resulting in unevenness on the surface of the finished product. Also, as can be seen from a comparison between Example 4 and Comparative Example 5, when the maleic acid monomer unit content exceeds the upper limit, even if metal ions are simultaneously contained, the surface properties are still not ideal. Without being bound by any particular theory, this result is likely due to the fact that the metal ion content is insufficient to stabilize compositions containing high amounts of maleic acid monomer units, and increasing the metal ion content would result in the generation of more of the above-mentioned impurities.

[0078] In other words, as shown in Examples 1 to 6 of the present application, the present invention preferably controls the maleic acid monomer unit content of the EVOH composition to 0.05-0.49 mol % and the copper metal content to 0.05-100 ppm, so that the composite fabrics thus produced not only have good wash resistance but also have ideal surface properties (the surface is smooth).

[0079] In short, the EVOH composition of the present invention, when distributed on a fabric or fiber, can not only reduce the impact of cool feeling caused by washing, but also improve the washing resistance, and has good surface properties.

[0080] All ranges provided herein are intended to include each specific range within the stated range, and combinations of subranges between the stated ranges. Also, any range explicitly stated herein includes its endpoints unless otherwise specified. Thus, the range 1-5 specifically includes 1, 2, 3, 4, and 5, as well as subranges 2-5, 3-5, 2-3, 2-4, 1-4, etc.

[0081] All publications and patent applications cited in this specification are herein incorporated by reference and for all purposes are to the same extent as if each individual publication or patent application was specifically and individually indicated to be incorporated by reference herein. In the event of a conflict between the present specification and a publication or patent application incorporated by reference herein, the present specification shall control.

[0082] Although the present invention has been described in detail above, what has been described above is only a preferred embodiment of the present invention, and is not limited to the scope of the present invention. Of course, equivalent modifications and adaptations based on the claims of the present invention are included within the scope of protection of the present invention.

Claims

1. An ethylene-vinyl alcohol copolymer (EVOH) composition comprising an ethylene-vinyl alcohol copolymer modified with maleic acid monomer units and a metal ion.

2. The composition according to claim 1, wherein the maleic acid monomer unit content is from 0.05 to 0.49 mol %.

3. 2. The composition according to claim 1, wherein the maleic acid monomer unit content is from 0.1 to 0.49 mol %.

4. The composition according to claim 1, wherein the metal ion content is 0.05 to 100 ppm.

5. The composition according to claim 1, wherein the metal ion content is 0.1 to 80 ppm.

6. The composition of claim 1 , wherein the metal ion is a copper ion.

7. 7. The composition of claim 6, wherein the metal ion is a divalent copper ion.

8. 2. The composition of claim 1, wherein the ethylene content of the composition is from 24 to 48 mole percent.

9. The composition of claim 1 , wherein the degree of saponification of the composition is greater than 99.5 mol %.

10. The composition of claim 1, wherein the volatile content of the composition is from 10 to 90%.

11. Textiles and A composition according to any one of claims 1 to 10 distributed on the fabric. A composite fabric comprising: The change rate of the cooling sensation parameter of the composite fabric after washing is 5% or less, the cooling sensation parameter is measured in accordance with the method described in FTTS-FA-019-2013, and the change rate of the cooling sensation parameter after washing is calculated by the following formula, in which L0 is the cooling sensation parameter after 0 washings, L30 is the cooling sensation parameter after 30 washings, and the washing is performed in accordance with the method described in JIS L 0217-103. composite fabric [0010]

12. The composite fabric of claim 11 , wherein the composition is applied to a surface of the fabric.

13. 12. The composite fabric of claim 11, wherein the fabric is impregnated with the composition so as to distribute the composition throughout the fabric.

14. 12. The composite fabric of claim 11, wherein the fabric is woven from any one of nylon, polyethylene, polyester, rayon, and natural fibers, or mixtures thereof.

15. The composite fabric of claim 12, wherein the composition is prepared in a 3-10% by weight solution and then distributed on the fabric.

16. A composite fiber comprising fibers and the composition according to any one of claims 1 to 10, wherein the fibers are impregnated with the composition so as to distribute the composition on the fibers. Composite Fiber

17. A woven fabric comprising the composite fiber of claim 16.

Citation Information

Patent Citations

  • Cross-linkable aqueous dispersion and its production method, and adhesive and coating agent

    JP2008184495A

  • Ethylene-vinyl alcohol copolymer resin composition, ethylene-vinyl alcohol copolymer film formed therefrom, and multilayer structure containing the same

    JP2022191991A

  • Highly absorbent composite fibre, highly absorbent non-woven fabric, and article comprising same

    WO2022080953A1